Psychiatric morbidity as a risk factor for hospital inpatients' safety: a cross-sectional study. (15th July 2019) - Mutti, Roberta; Montali, Francesca; Ferrari, Antonio; Nouvenne, Antonio; Lauretani, Fulvio; Campaniello, Giovanna; Marchesi, Carlo
Very few studies have shown the relation between psychiatric morbidity and hospital care safety. Some studies emphasise the importance of proper management of care safety for patients treated in psychiatric settings. Therefore, it is of great importance to deeply analyse the psychiatric morbidity impact on the safety of patient care in non-psychiatric settings. A cross-sectional study has been carried out, based on a simple random sample of N = 941 psychiatric consultations collected over a three-year period (2012-014) representative of N = 4548, sent to the intensive psychiatric hospital service by the wards of a university hospital. Demographic characteristics and psychiatric morbidity of hospital inpatients are associated with the four main outcomes/events due to the patients' active participation in the care processes (patient fall, patients' departure, suicide attempt or self-harm and acts of violence against professionals).